2021
DOI: 10.7717/peerj.12527
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experience of switching from tenofovir disoproxil fumarate to tenofovir alafenamide in patients with chronic hepatitis B: a retrospective study

Abstract: Background Tenofovir alafenamide (TAF) has good viral suppression efficacy and less adverse effect than tenofovir disoproxil fumarate (TDF). Real-world studies on the antiviral efficacy and safety of switching from TDF to TAF in patients with chronic hepatitis B (CHB) are limited. Methods This retrospective study included 167 nucleos(t)ide analogue (NA)-naive patients with CHB. All the patients received TDF at least 12 months before switching and TAF at least 12 months after switching at a single medical cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
5
11
0
Order By: Relevance
“…As it has been reported in all previous studies, 4,5,10–13 TAF maintained virological suppression defined by undetectable serum HBV DNA in the vast majority (99%) of cases who started TAF without detectable viremia and achieved virological suppression in most (90% or 26/29) switched or naive patients who started TAF with detectable serum HBV DNA. Whether suboptimal initial response and/or compliance issues were responsible for the small proportion of patients with detectable HBV DNA at 12 months of TDF cannot be determined, but viremia levels were always low at 12 months and all (100%) patients remaining under follow‐up achieved HBV DNA undetectability at 24 months of TAF therapy.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…As it has been reported in all previous studies, 4,5,10–13 TAF maintained virological suppression defined by undetectable serum HBV DNA in the vast majority (99%) of cases who started TAF without detectable viremia and achieved virological suppression in most (90% or 26/29) switched or naive patients who started TAF with detectable serum HBV DNA. Whether suboptimal initial response and/or compliance issues were responsible for the small proportion of patients with detectable HBV DNA at 12 months of TDF cannot be determined, but viremia levels were always low at 12 months and all (100%) patients remaining under follow‐up achieved HBV DNA undetectability at 24 months of TAF therapy.…”
Section: Discussionsupporting
confidence: 81%
“…The above findings were also confirmed in subsequent phase III trials in China 9 . In two US and one Taiwanese cohort studies including mostly patients with normal renal function, 10–12 eGFR was reported to stabilise at 48 weeks after switching to TAF while it was declining during previous TDF therapy. It should be noted, however, that eGFR changes should be always considered in relation to the characteristics of the patient population and especially the baseline eGFR levels and whether TAF is used in untreated or NA switched patients.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Chronic hepatitis C virus (HCV) infection is one of the common causes of liver cirrhosis and liver cancer that can now be prevented by effective antiviral therapy [ 1 , 2 , 3 , 4 , 5 , 6 ]. Over the past two decades, interferon-based therapy was the standard of care; however, its use is limited to numerous treatment-related side effects, the risk of liver decompensation among cirrhotic patients, and the need to understand the genotype of HCV to determine the treatment duration.…”
Section: Introductionmentioning
confidence: 99%